Factors that influence saving behavior among undergraduates at UiTM Melaka City Campus / Nurul Azlin Jelani - Jelani, Nurul Azlin (2015)
Personal financial planning is very important because it will determine a person’s financial success. Financial management for all people are varies around the world and the most common one is saving. The purpose of this research is to study the factors that influence saving behavior among undergraduates at UiTM Melaka City Campus. Therefore, the research objectives in this study are to identify which factors that most influence saving behavior, to determine the relationship between Self-Control and Saving Behavior, to examine the relationship between Financial Literacy and Saving Behavior, and to identify the relationship between Parental Socialization with Saving Behavior among undergraduates at UiTM Melaka City Campus. This research use primary data. Primary data are collected using questionnaires. The questionnaires are developed using multiple choices and five (5) point Likert scale. 200 questionnaires have been distributed to all students that come from semester 1 until semester 5 in Faculty of Business Management. The sampling procedure adopted was Stratified Random Sampling technique. The data obtained were analyzed using Statistical Package for Social Science (SPSS). Moreover, Frequency Analysis, Reliability Analysis, Pearson Correlation and Multiple Regression Analysis are used for the data analysis method. Based on findings in this study, it shows that there is a significant positive relationship exists between Saving Behavior towards Self-Control, Financial Literacy and Parental Socialization as the p-value is less than 0.05.